2017
DOI: 10.7860/jcdr/2017/26790.10353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IOTA Simple Ultrasound Rules to Distinguish Benign and Malignant Ovarian Tumours

Abstract: IOTA simple ultrasound rules were highly sensitive and specific in predicting ovarian malignancy preoperatively yet being reproducible, easy to train and use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 9 publications
7
43
1
2
Order By: Relevance
“…12,13 If inconclusive results are considered as malignant sensitivity index increased from 92.8% to 94% and specificity decreased from 93% to 87% respectively. The result well correlated with the study of Timmerman D et al, Alcazar et al, Nunes et al, Garg et al and Tantipalakorn C et al 8,[13][14][15][16]…”
Section: Resultssupporting
confidence: 91%
“…12,13 If inconclusive results are considered as malignant sensitivity index increased from 92.8% to 94% and specificity decreased from 93% to 87% respectively. The result well correlated with the study of Timmerman D et al, Alcazar et al, Nunes et al, Garg et al and Tantipalakorn C et al 8,[13][14][15][16]…”
Section: Resultssupporting
confidence: 91%
“…They reported that the simple rules were applicable in 236 (87%) masses, with 90.6% sensitivity and 95.3% specificity. Garg et al . also evaluated the efficacy of the IOTA simple rules as a tool in the early diagnosis of ovarian malignancies and concluded that it was applicable in 45 (90%) cases with 91.6% sensitivity, 84.5% specificity, and 84.5% accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Both image orientations are used in clinical practice and the image orientation is a frequent topic of debate . There are several good reasons to determine whether one orientation should be recommended.…”
Section: Introductionmentioning
confidence: 99%